Chapter 26 Language technology approach to "seeing" in Akkadian - Sahala, Aleksi (Taylor & Francis, 2022)
One of the ways meanings of words can be understood is based on their distributional properties. Such methodology offers an interesting quantitative viewpoint on the study of the lexicography of long-extinct languages. This chapter explores the use of Pointwise Mutual Information (PMI), a well-known statistical word association measure used in collocation analysis. PMI is applied to the data in order to gain insights on the semantic nuances of Akkadian verbs of seeing (amāru, naṭālu, palāsu, dagālu, ḫiātu, barû, and subbû). To evaluate the data-driven results, the findings are compared to previous philological work by Ainsley Dicks. The analysis of the top-ranked PMI-extracted collocates provides a good overview of the typical semantic differences between the seven verbs of interest.